(untitled) (Communications in Mathematical Research, 2021)
In this paper, K-controllability and approximate K-controllability of non-linear neutral differential equations in Banach spaces are studied. Sufficient conditions are established for each of these types of controllability. The results are obtained by using Leray-Schauder theory.